2004
DOI: 10.1038/oby.2004.196
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening of the 11β‐HSD1 Gene in Men Characterized by the Metabolic Syndrome

Abstract: Adipose tissue type 1 11β‐hydroxysteroid dehydrogenase (11β‐HSD1), which generates hormonally active cortisol from inactive cortisone, has been shown to play a central role in adipocyte differentiation and abdominal obesity‐related metabolic complications. The objective was to investigate whether genetic variations in the human 11β‐HSD1 gene are associated with the metabolic syndrome among French‐Canadian men. We sequenced all exons, the exon‐intron splicing boundaries, and 5′ and 3′ regions of the human 11β‐H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…However, several other studies have failed to find evidence of an association between HSD11B1 polymorphisms and type 2 diabetes, obesity, or metabolic syndrome [18][19][20][21].…”
Section: Laboratory Analysismentioning
confidence: 99%
“…However, several other studies have failed to find evidence of an association between HSD11B1 polymorphisms and type 2 diabetes, obesity, or metabolic syndrome [18][19][20][21].…”
Section: Laboratory Analysismentioning
confidence: 99%
“…It was also reported that the polymorphism ins4436A in intron 3 was associated with greater body mass, central obesity and insulin resistance in obese Caucasian children [21]. However, there are other studies showing no association between polymorphisms in the HSD11B1 gene and diabetes or obesity in Caucasians [22,23,24]. In our study, we could not find any association between common SNPs of HSD11B1 and type 2 diabetes, although the statistical power for g.+27447G > C and g.+27810C > T was not sufficient to be conclusive of a negative association between these SNPs and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that single-nucleotide polymorphisms (SNPs) of the HSD11B1 gene are associated with type 2 diabetes mellitus and insulin resistance in Pima Indians [20] and obesity and insulin resistance in Caucasian children [21]. In contrast, several studies showed no association between polymorphisms of HSD11B1 and body composition or glucose metabolism in Caucasians [22,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we cannot exclude that the HSD11B1 variants investigated in our study are of no functional significance. As a matter of fact, lack of association between HSD11B1 gene polymorphisms and metabolic complications of obesity was reported in adult populations of French Canadians, Japanese and elderly Dutch [24,35,36]. Still, other gene variants might be implicated in development of MetS traits.…”
Section: Discussionmentioning
confidence: 99%